~tslil/univalence-to-funext

ref: refs/heads/master univalence-to-funext/Univalence-to-funext.agda -rw-r--r-- 8.7 KiB View raw
35576e52 — tslil clingman Fixed links 1 year, 23 days ago
                                                                                
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
{-# OPTIONS --without-K --rewriting #-}

module Univalence-to-funext where

open import lib.Base
open import lib.Equivalence
open import lib.Function
open import lib.PathGroupoid
open import lib.PathFunctor
open import lib.NType

--============================================================================--
--                      Generic paths in Σ types

module _ {i j} {A : Type i} {B : A  Type j} where
  Σ-path-pair : (v w : Σ A B)  Type (lmax i j)
  Σ-path-pair v w = Σ (fst v == fst w)
                      (λ p  transport B p (snd v) == snd w)

  pair→Σ= : {v w : Σ A B}  Σ-path-pair v w  v == w
  pair→Σ= (idp , idp) = idp

  Σ=→pair : {v w : Σ A B}  v == w  Σ-path-pair v w
  Σ=→pair idp = (idp , idp)

  Σ=→pair→Σ= : {v w : Σ A B} (p : v == w)  pair→Σ= (Σ=→pair p) == p
  Σ=→pair→Σ= idp = idp

  pair→Σ=→pair : {v w : Σ A B} (z : Σ-path-pair v w) 
                 Σ=→pair (pair→Σ= z) == z
  pair→Σ=→pair (idp , idp) = idp

  Σ=≃pair : {v w : Σ A B}  (v == w)(Σ-path-pair v w)
  Σ=≃pair = equiv Σ=→pair pair→Σ= pair→Σ=→pair Σ=→pair→Σ=


--============================================================================--
--                           Univalence

idtoeqv :  {i} {A B : Type i}  (A == B)  (A ≃ B)
idtoeqv {A = A} idp = ide A

postulate
  ua :  {i} {A B : Type i}  (A ≃ B)  (A == B)
  idtoeqv-ua-β :  {i} {A B : Type i} (e : A ≃ B)  idtoeqv (ua e) == e

eqv-post∘ :  {i} {A B : Type i} {C : Type i} (p : A == B) 
            fst (idtoeqv (ap (λ T  (C  T)) p)) == _∘_ (fst (idtoeqv p))
eqv-post∘ idp = idp

--============================================================================--
--                         Happly and lemmas

module _ {i j} {A : Type i} {B : A  Type j} {f g : Π A B} where
  idh : f ∼ f
  idh a = idp

  happly : f == g  f ∼ g
  happly p a = ap (λ k  k a) p

  tr-happly-lemma : (p : f == g) 
                    transport (λ k  f ∼ k) p (idh) == happly p
  tr-happly-lemma idp = idp

  fib-happly-lemma : (h : f ∼ g)  ((f , idh) == (g , h)) ≃ hfiber happly h
  fib-happly-lemma h = (equiv from to α β) ∘e Σ=≃pair
    where
      to : hfiber happly h  Σ-path-pair (f , idh) (g , h)
      to (p , q) = (p , tr-happly-lemma p ∙ q)

      from :  Σ-path-pair (f , idh) (g , h)  hfiber happly h
      from (p , q) = (p , ! (tr-happly-lemma p) ∙ q)

      β : (b : Σ-path-pair (f , idh) (g , h))  to (from b) == b
      β (p , q) = pair→Σ= (idp , ! (∙-assoc (tr-happly-lemma p)
                                            (! (tr-happly-lemma p)) q) ∙
                                 !-inv-r (tr-happly-lemma p) ∙2 idp)

      α : (a : hfiber happly h)  from (to a) == a
      α (p , q) = pair→Σ= (idp ,
                           ! (∙-assoc (! (tr-happly-lemma p))
                             (tr-happly-lemma p) q) ∙
                           !-inv-l (tr-happly-lemma p) ∙2 idp)

--============================================================================--
--                     Equivalences and contractibility

contr-retract :  {i} {A B : Type i}
                (r : A  B) (s : B  A) 
                (r ∘ s ∼ (idf B)) 
                is-contr A  is-contr B
contr-retract r s h p = has-level-in
                      ((r (fst c)) , λ y  ap r (snd c (s y)) ∙ h y)
                      where c = has-level-apply p

module _ {i j} {A : Type i} {B : Type j} where
  is-contr-map : (f : A  B)  Type (lmax i j)
  is-contr-map f = (y : B)  is-contr (hfiber f y)

  tr-ap-lemma : (f : A  B) {a' a : A} {b : B}
                (p : a' == a) (q : f a' == b) 
                transport (λ x  f x == b) p q == ! (ap f p) ∙ q
  tr-ap-lemma f idp idp = idp

  nat-lemma : {k l : B  B} {a b : B} (p : a == b )(h : k ∼ l) 
              ap k p ∙ h b == h a ∙ ap l p
  nat-lemma {a = a} idp h = ! (∙-unit-r (h a))

  contr-map-is-equiv : {f : A  B}  (is-contr-map f  is-equiv f)
  contr-map-is-equiv {f = f} c = snd (equiv f g α β)
    where
      g : B  A
      g b = fst (fst (has-level-apply (c b)))

      α : f ∘ g ∼ (idf B)
      α b = snd (fst (has-level-apply (c b)))

      β : g ∘ f ∼ (idf A)
      β a = fst (Σ=→pair (snd (has-level-apply (c (f a))) (a , idp)))



  equiv-is-contr-map : {f : A  B}  (is-equiv f  is-contr-map f)
  equiv-is-contr-map {f = f} e b =
                        has-level-in (hf , λ y  pair→Σ= (fc y , sc y))
    where
      g : B  A
      g = is-equiv.g e

      α : g ∘ f ∼ (idf A)
      α = is-equiv.g-f e

      β : f ∘ g ∼ (idf B)
      β = is-equiv.f-g e

      hf : hfiber f b
      hf = ((g b) , (β b))

      fc : (y : hfiber f b)  (g b) == fst y
      fc (a , p) = ap (g) (! p) ∙ α a

      sc : (y : hfiber f b) 
           transport (λ x  f x == b) (fc (fst y , snd y)) (β b) == snd y
      sc (a , p) =
        transport (λ x  f x == b) (fc (a , p)) (β b)
          =⟨ tr-ap-lemma f (fc (a , p)) (β b) ⟩
        ! (ap f  (fc (a , p)))(β b)
          =⟨ ap ! (ap-∙ f (ap g (! p)) (α a)) ∙2 idp ⟩
        ! (ap f (ap g (! p)) ∙ ap f (α a))(β b)
        =⟨ ap ! (idp {a = ap f (ap g (! p))} ∙2 is-equiv.adj e a) ∙2
           idp {a = β b} ⟩
        ! (ap f (ap g (! p))(β (f a)))(β b)
          =⟨ ap ! (∘-ap f g (! p) ∙2 idp) ∙2 idp ⟩
        ! (ap (f ∘ g) (! p)(β (f a)))(β b)
          =⟨ !-∙ (ap (f ∘ g) (! p)) (β (f a)) ∙2 idp ⟩
        (! (β (f a)) ∙ ! (ap (λ x  f (g x)) (! p)))(β b)
          =(idp {a = ! (β (f a))} ∙2 !-ap (f ∘ g) (! p)) ∙2 idp {a = β b}(! (β (f a))(ap (f ∘ g) (! (! p))))(β b)
          =(idp {a = ! (β (f a))} ∙2 ap (ap (f ∘ g)) (!-! p)) ∙2
             idp {a = β b}(! (β (f a))(ap (f ∘ g) p))(β b)
          =⟨ ∙-assoc (! (β (f a))) (ap (f ∘ g) p) (β b) ⟩
        ! (β (f a))(ap (f ∘ g) p ∙ (β b))
         =⟨ idp {a = ! (β (f a))} ∙2
            (nat-lemma p β ∙ idp {a = β (f a)} ∙2 ap-idf p) ⟩
        ! (β (f a))(β (f a) ∙ p)
          =⟨ ! (∙-assoc (! (β (f a))) (β (f a)) p)(! (β (f a)) ∙ β (f a)) ∙ p
          =⟨ !-inv-l (β (f a)) ∙2 idp ⟩
        p
          =∎

--============================================================================--
--                        Univalence implies funext

module _ {i} {A : Type i} {B : A  Type i} {f : Π A B} where
  image : A  Type i
  image a = Σ (B a) (λ b  f a == b)

  graphType : Type i
  graphType = Σ A image

  prA : graphType  A
  prA = fst

  prA-is-equiv : graphType ≃ A
  prA-is-equiv = equiv prA (λ x  (x , f x , idp)) (λ b  idp) β
    where
      tr-post-concat :  {i} {X : Type i} {x y z : X} {p : x == y}
                 (q : z == x)  transport (_==_ z) p q == q ∙ p
      tr-post-concat {p = idp} idp = idp

      β : (a : graphType)  (fst a , f (fst a), idp) == a
      β (a , b , p) = pair→Σ= (idp , (pair→Σ= (p , (tr-post-concat idp))))

  fibreOverId : Type i
  fibreOverId = hfiber (_∘_ prA) (idf A)

  fibreOverId-is-contr : is-contr fibreOverId
  fibreOverId-is-contr = prA∘-is-equiv (idf A)
       where
        p : graphType == A
        p = ua prA-is-equiv

         : fst (idtoeqv p) == prA
        pβ = ap fst (idtoeqv-ua-β prA-is-equiv)

        prA∘-is-equiv : is-contr-map (λ g  prA ∘ g)
        prA∘-is-equiv = transport is-contr-map
                         (eqv-post∘ p ∙ ap (λ x  _∘_ x))
                         (equiv-is-contr-map
                           (snd (idtoeqv (ap (λ T  (A  T)) p))))

  homotopyType : Type i
  homotopyType = Σ (Π A B) (λ g  f ∼ g)

  -- We crucially make use of the η-rule for functions here
  s : homotopyType  fibreOverId
  s (g , h) = ((λ a  (a , g a , h a)) , idp)

  r : fibreOverId  homotopyType
  r (func , p) = fst ∘ img , snd ∘ img
               where
                 img : (a : A)  image a
                 img a = transport image (happly p a) (snd (func a))

  -- and here
  var-funext : is-prop homotopyType
  var-funext = contr-is-prop (contr-retract r s (λ _  idp)
                              fibreOverId-is-contr)

module _ {i} {A : Type i} {B : A  Type i} {f g : Π A B} where
  pre-funext : (h : f ∼ g)  is-contr ((f , idh {g = g}) == (g , h))
  pre-funext h = has-level-apply var-funext (f , idh {g = g}) (g , h)

  funext : is-equiv (happly {f = f}{g = g})
  funext = contr-map-is-equiv
             λ h  equiv-preserves-level
                     (fib-happly-lemma h)
                     ⦃ pre-funext h ⦄